Implementasi Workshop Gemini AI untuk Guru SMP dan MI sebagai upaya Mendukung Pembelajaran Meaningful, Mindful, Joyful - Aripin; Suhendi, Herni Yuniarti; Sujarwanto, Eko; Surahman, Endang; Ardiansyah, Ryan (KARISMAS - JURNAL PENGABDIAN KARYA INOVASI MASYARAKAT, 2025)
Educators at Nurul Yaqin Islamic Junior High School and Cihuni Islamic Junior High School in Tasikmalaya Regency face challenges in utilizing Artificial Intelligence (AI) for in-depth learning due to limited understanding and practical skills. This community service activity aims to improve teacher competency in utilizing AI to create meaningful, enjoyable, and conscious learning. The method used is a participatory approach involving 20 teachers in a series of activities from July to November 2025, including socialization, intensive training, workshops on the use of Gemini AI, implementation, and mentoring. Evaluation used pre-test and post-test instruments to measure competency improvement. The pre-test results showed that initial pedagogical understanding was better than technical mastery of AI, with weaknesses in exploring advanced features and joyful learning strategies. After training, the post-test results showed a significant increase in understanding and skills in using Gemini AI, especially in aspects of processing teaching device results (score 1.00) and feature utilization (0.96). Understanding of meaningful (0.96) and joyful (0.85) pedagogical concepts also increased significantly, although the mindfulness aspect (0.67) still requires further strengthening. This activity was highly positive among participants and successfully addressed partner issues, serving as a model for effective and sustainable AI technology implementation in rural schools